C-reactive protein as predictor of anastomotic complications after minimally invasive oesophagectomy - Prochazka, Vladimir; Marek, Filip; Kunovsky, Lumir; Svaton, Roman; Farkasova, Martina; Potrusil, Martin; Moravcik, Petr; Kala, Zdenek (Journal of minimal access surgery, 2019)
BACKGROUND: Anastomotic leaks after oesophagectomy with tabularised stomach replacement are a significant factor in post-operative mortality and morbidity. Early detection and treatment of this complication allow for improving operative and oncological results. When assessing laboratory values - elevation of inflammatory parameters - complicated interpretation is an issue (systemic inflammatory response syndrome, surgical versus non-surgical complication). Results studying the relationship between C-reactive protein (CRP) and complications following oesophagectomies are inconsistent. The aim of our work was to find relationships between the development of post-operative CRP values and the occurrence of anastomotic complications following minimally invasive oesophagectomy (MIE). MATERIALS AND METHODS: Analysis of the relationship between CRP values and the occurrence of anastomotic complications or the necessity of reoperation following oesophagectomy with tabularised stomach replacement and cervical anastomosis performed using thoracoscopy and laparoscopy in a group of patients operated on for malignancies at our department between 2012 and 2015. RESULTS: A significant difference was found in average CRP values on the 5th day and 7th day following operation between patients with and without leaks (233 mg/l vs. 122.8 mg/l P = 0.003, respectively 208.9 mg/l vs. 121.3 mg/l P = 0.014). However, on the 5th day, the leak was clinically apparent only in one case out of 11 leaks. A significant difference in CRP values on the 5th day was found between patients who needed revision surgery and patients without revision surgery (294 mg/l vs. 133.5 mg/l P = 0.01). CONCLUSIONS: Patients after MIE with tabularised stomach replacement and cervical anastomosis complicated by anastomotic leaks or with the necessity for reoperation had a significantly higher CRP values on the 5th day following operation than patients without complications, regardless of the presence of clinical signs of leaks.
Keywords: Anastomotic leak; C-reactive protein; oesophagal carcinoma; minimally invasive oesophagectomy